The Management of Combined Antithrombotic Therapy in Patients With Atrial Fibrillation Undergoing Percutaneous Coronary Intervention: A Particularly Complex Challenge, Especially in the Elderly - Bencivenga, Leonardo; Komici, Klara; Corbi, Graziamaria; Cittadini, Antonio; Ferrara, Nicola; Rengo, Giuseppe (Frontiers in Physiology, 2018)
Anticoagulation is superior to dual antiplatelet therapy in the prevention of thromboembolic events in patients with atrial fibrillation, otherwise the prevention of ischemic risk and stent thrombosis after percutaneous coronary intervention is warranted by dual antiplatelet therapy. The coexistence of conditions requiring combined antithrombotic therapies is becoming an increasing relevant clinical problem, whose therapeutic management has long been found in the medical experience rather than in guidelines and consensus. Recently, updates in guidelines and relevant studies have been published in order to better clarify the best management of combined antithrombotic therapy. In the present review, we have analyzed the recent literature, underlining the progresses and the residual limits of the most up-to-date evidence on the management of patients requiring dual or triple antithrombotic therapy, due to coexisting atrial fibrillation and coronary artery disease. An in-depth overview is also focused on the management of antithrombotic therapy in the elderly patient, which represents an even more complex challenge for the clinician. This is due to the high prevalence, among over 65 years aged people, of conditions requiring association of antiplatelet and anticoagulant drugs, the numerous comorbidities, the higher risk of complications, such as bleedings, and the lack of specific evidence, especially for the frail elderly. Nowadays, triple therapy (oral anticoagulation plus dual antiplatelet agents) for the shortest possible time should be the treatment for atrial fibrillation patients undergoing percutaneous coronary intervention, whereas dual therapy (single antiplatelet plus oral anticoagulation) may be preferred for patients at high bleeding risk.